An investigation on the effect of alcoholic and aqueous extracts of Dorema aucheri (Bilhar) on some pathogenic bacteria in vitro - Tabatabaei Yazdi, Farideh; Alizadeh Behbahani, Behrooz; Vasiee, Alireza; Mortazavi, Seyed Ali; Tabatabaei Yazdi, Forouzan (Archives of Advances in Biosciences, 2015)
Dorema aucheri is a plant that grows in Iran. In Persian it is called (Bilhar). This experimental study was carried out at Ferdowsi University of Mashhad in 2014. After collection and preparation of aqueous and ethanolic extracts of Dorema aucheri (Bilhar), The antibacterial activity of ethanolic and aqueous extracts of Bilhar was evaluated against 7 laboratory strains of microorganisms, including 4 Gram positive (Staphylococcus aureus, Streptococcus pyogenes, Bacillus cereus and Bacillus subtilis) and 3 Gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Proteus vulgaris). Its effects against human pathogen microorganism were determined using “Spreading of the Extract on Medium Surface” and “Disk Agar Diffusion Method”, Minimal Inhibitory Concentration (MIC) and Minimum Lethal Concentration (MLC) were determined for this extract. Collected data were analyzed by SPSS software using one-way ANOVA. The zone of inhibition for the ethanolic extract varied from 8 mm for P. aeruginosa to 24 mm for S. pyogenes and from 7 mm for P. aeruginosa to 19 mm for S.pyogenes in the aqueous extract. The minimum inhibitory concentration (MIC) of the extracts ranged between 2 mg/ml and 64 mg/ml while the minimum lethal concentration (MLC) ranged between 4 mg/ml and 256 mg/ml. Among of tested strains, P. aeruginosa has maximum MIC and MBC. 30 and 40 mg/mL Concentrations of Redcurrant have significant antimicrobial effect on bacteria. Antibacterial effect of extracts was decreased with decrease of extract concentration in disk. According to result, ethanolic extract of Dorema aucheri have antimicrobial effect on growth of all of the strains exposed analyzes and antimicrobial effect of that was maximum on Gram-positive bacterum of S. pyogenes. P. aeruginosa showed the highest level of resistance against the aqueous and ethanolic Bilhar extracts. The present study demonstrated that the ethanol leaf extract of Dorema aucheri hold an excellent potential as an antibacterial agent.